AGE OF LATE QUATERNARY MARINE DEPOSITS OF SOUTHERN ITALY DETERMINED BY AMINOSTRATIGRAPHY, FAUNAL CORRELATION, AND URANIUM-SERIES DATING (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Numerous studies on the 40 to 60 meter strandline at Capo Milazzo, Sicily, yielded no consensus on its place in the Pleistocene sea level chronology; it has been considered to be Sicilian, mid— Pleistocene Milazzian stage, and also Eutyrrhenian. In light of this controversy, we measured amino acid D—alloisoleucine to L—isoleucine ratios (alle/ile) in shells at Capo Milazzo and at other related marine sites in southern Italy. We calibrated amino acid ratios at Mare Piccolo (Taranto) by uranium—series dating of corals to represent 122 ± 4000 years B.P. Using the calibrated amino acid ratios and paleontologic evidence, we correlated the 40—60 m strandline at Capo Milazzo with last interglacial Eutyrrhenian or isotopic Stage 5 deposits near Reggio Calabria (Ravagnese and Bovetto), Messina (Capo Peloro) and at Mare Piccolo, southern Italy. Assuming a constant uplift rate and an initial sea level of + 6 during stage 5e, we calculated the average uplift rate at Bovetto to be 0.99 m/ 1000 years over the past 125,000 years, The shoreline edge has not been located at Milazzo, Ravagnese and Capo Peloro, so only minimum uplift rates are calculated.
Keywords: Amino acid geochronology; Pleistocene; Tyrrhenian; Sicilia; Calabria.